Physical and mechanical properties of tilapia scale hydroxyapatite-filled high-density polyethylene composites - Aiza Jaafar, C. N.; Zainol, I.; Izyan Khairani, M. I.; Dele-Afolabi, T. T. (MDPI, 2022)
The effects of filler loading and silane coupling agent on the properties of hydroxyapatite (HAp)-filled high density polyethylene (HDPE) composites have been studied. The (HAp) powder was successfully produced from tilapia scales using the spray drying process utilized to prepare the HDPE/HAp composites. The FTIR peaks for the untreated HDPE/30HAp composite corresponded to the functional groups of HDPE (C-CH3) and –CH2 and HAp (PO4−3 and O-H). The FTIR spectrum for the silane-treated composite showed that the C=O and silanol groups were eliminated, which strongly confirms the chemical interaction between the HAp fillers and the HDPE matrix. The developed composites demonstrated enhanced mechanical performance, and in particular the treated HDPE/30HAp-S composite exhibited superior tensile strength, Young’s modulus and flexural modulus of 28.26 MPa, 1272 MPa and 796 MPa, respectively. In vitro cytotoxicity analysis showed that the developed composites were non-toxic and have great potential to be used for biomedical application.